Genome Replication in Thermococcus kodakarensis Independent of Cdc6 and an Origin of Replication - Gehring, Alexandra M.; Astling, David P.; Matsumi, Rie; Burkhart, Brett W.; Kelman, Zvi; Reeve, John N.; Jones, Kenneth L.; Santangelo, Thomas J. (Frontiers in Microbiology, 2017)
The initiation of DNA replication is typically tightly regulated by proteins that form initiation complexes at specific sequences known as replication origins. In Archaea and Eukaryotes, Cdc6, a near-universally conserved protein binds and facilitates the origin-dependent assembly of the replicative apparatus. TK1901 encodes Cdc6 in Thermococcus kodakarensis but, as we report here, TK1901 and the presumed origin of replication can be deleted from the genome of this hyperthermophilic Archaeon without any detectable effects on growth, genetic competence or the ability to support autonomous plasmid replication. All regions of the genome were equally represented in the sequences generated by whole genome sequencing of DNA isolated from T. kodakarensis strains with or without TK1901, inconsistent with DNA initiation occurring at one or few origins, and instead suggestive of replication initiating at many sites distributed throughout the genome. We were unable to generate strains lacking the recombination factors, RadA or RadB, consistent with T. kodakarensis cells, that are oligoploid (7-19 genomes per cell), employing a recombination-based mechanism of DNA replication. Deletion of the previously presumed origin region reduced the long-term viability of cultures supporting the possibility that retaining an origin-based mechanism of DNA initiation provides a survival mechanism for stationary phase cells with only one genome.